INTERPERSONAL COMMUNICATION STRATEGY OF BADMINTON TRAINER IN INCREASING THE MOTIVATION OF WOMEN'S DUAL ATHLETES DJARUM JAKARTA DURING THE COVID-19 PANDEMIC - Nadia Nerissa; Ririn Puspita Tutiasri (Universitas Islam Balitar, 2022)
Interpersonal communication of badminton coaches has a role in growing the confidence of women's doubles athletes to increase motivation in training activities. Because during training activities, women's doubles athletes experience a decrease in confidence during the COVID-19 pandemic which has an impact on physical condition and performance. The research method used in this study is a qualitative research using McClelland's theory of motivation. The data collection of this research was collected by interview, informants were five badminton coaches and five women's doubles athletes at the Djarum Badminton Association Jakarta. The results of this study indicate that interpersonal communication used by coaches and women's doubles athletes can prove that interpersonal communication can be used to convey messages with the occurrence of proximity to get the results directly. In accordance with McClelland's motivational theory, the need for achievement provides a strategy regarding mastery of playing techniques during training activities as an understanding of achieving achievements and athlete benchmarks so that relationships can be established, affiliation plays a role in growing the athlete's social spirit as self-confidence that is intertwined by increasing motivation during the COVID-19 pandemic. 19, the power of fostering women's doubles athletes to have a leadership spirit and responsibility for their own personality.